CERVICAL EWING’S SARCOMA-OUR EXPERIENCE WITH REVIEW OF LITERATURE - DR. BUDDHADEV SAHA; DR. SAYANTIKA SARKAR; DR. EKTA AGARWAL; DR. N.N. BHAUMIK (International Journal of Pharma and Bio Sciences, 2016)
Ewing’s sarcoma is the second most common primary bone malignancy in children after osteosarcoma. It is usually seen in the metaphyses of long bones. Primary ES of the spine are rare. Spinal Ewing sarcoma most commonly seen in sacrococcygeal region and it rarely involves the cervical spine. Similar features between Ewing’s sarcoma and Caries Spine makes it a difficult diagnosis. They discussed the case of a 14 year old female Muslim child presented with features of cervical myeloradiculopathy, likely of inflammatory etiology. Detailed examination and investigations went in favour of Caries spine leading to C5 and C6 Left hemi-laminectomy with excision of intraspinal extradural mass. But a histopathological report of surgical specimen, although not confirmatory of Ewing’s sarcoma, post operative clinical features proved it to be so. Hence a high degree of suspicion and Ewing’s sarcoma as a differential diagnosis must be kept in mind while treating any young patient presenting with features of Caries Spine.